Other Voices : a Study of the Late Poetry of Luis Cernuda - Coleman, Alexander (Baltimore, Maryland : Project Muse, 2018)
Coleman begins his book with the following supposition: that Luis Cernuda was a poet whose primary impulse in his art was the suppression of the subjective and the consequent objectivization of poetry.
I. Ars poetica -- II. Hölderlin and Cernuda -- III. Nature as symbol -- IV. The spirit in stone -- V. The projected voice -- VI. Personae -- VII. The final phase : the other.
Prepared as a doctoral dissertation, Columbia University, 1964.
Includes bibliographical references (pages 183-185).
Print version record.
JSTOR
Keywords: Cernuda, Luis; Cernuda, Luis; Cernuda, Luis; Electronic books